Employee Performance Factor Analysis at KSPPS BMT NUS (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2024)
This study aims to examine the employee performance at KSPPS BMT NU Sejahtera Semarang. The research method used was quantitative, with a population of 52 employees of KSPPS BMT NU Sejahtera Semarang. The sampling technique employed was saturation sampling. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results of the study indicate that Islamic organizational culture, compensation, and motivation have a significant positive influence on employee performance. Islamic organizational culture, compensation, and motivation collectively influence employee performance at KSPPS BMT NU Sejahtera Semarang with a regression coefficient of 68.1%, while the remaining percentage is influenced by other variables beyond the scope of this study. Based on the findings, several suggestions are provided for KSPPS BMT NU Sejahtera Semarang. It is important to enhance the implementation of Islamic values, provide appropriate compensation, and improve employee motivation. For future researchers, further studies can be conducted to identify other factors beyond the variables examined in this study that may influence employee performance. Comparative research with similar organizations or within the same sector can also be conducted to gain a more comprehensive understanding of the factors contributing to employee performance
Keywords: Islamic Organizational Culture, Compensation, Employee Performance, Motivation